INCREASING THE EFFECIENCY OF LASER MARKING OFALUMINUM ALLOYS BY DOUBLE WRITING OF THE SYMBOLS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
A comparison is made between samples marked by writing letters and symbols once, with these marked by twice but writing with two times greater velocity. As a consequence of the sharp decreasing of the main characteristic of the material –its reflective index, in the second case we received an enhancement of the effectiveness of the laser marking, decreasing energy use at the same time. Experimental studies have been carried out with a CuBr (copper bromide vapour) laser for specific mechanical engineering details.